Overcoming Numeracy Difficulties in MI Students: Educational Solutions to Improve National Assessment Outcomes - Kurniawan, Sugeng; Andryadi, Andryadi; Carli Wiseza, Fitria; Yulatas, M. Ali Yulatas (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study focuses on students' difficulties in learning numeracy at Madrasah Ibtidaiyah (MI) Alam Ya Bunayya Bungo. The main problem identified was the low ability of students to solve complex numeracy problems, which involved an understanding of in-depth mathematical concepts, procedural steps, and problem-solving skills. This study uses a qualitative approach with a case study design. Data was collected through in-depth interviews with students, teachers, and parents, participatory observation during classroom learning, as well as analysis of documentation, such as lesson plans and student work outcomes. Data analysis is carried out through three main stages, namely reduction, presentation, and data verification. The results showed that students' difficulties were caused by limited understanding of basic mathematics, less interactive teaching methods, and low support from families at home. Teachers tend to use traditional teaching methods that only emphasize memorization and mechanical procedures. On the other hand, students who were actively involved with visual aids, such as pictures and concrete objects, showed a better understanding of numeracy problems. Family support was also found to have a significant influence on students' motivation and confidence in learning. The implication of this study is the importance of adopting teaching methods based on direct experience and the use of visual aids in numeracy learning. In addition, synergy between teachers, schools, and parents needs to be improved to support students' academic success holistically. This study provides strategic recommendations for teachers and education policy makers to overcome gaps in numeracy learning